User's satisfaction and perception on imageability and legibility of government offices a comparative study of the key agencies in Panabo City - Hintay, Kathrine Jeanne D.; Malaque, Isidoro R. III (2023)
Enhancing the legibility and imageability of the front-line government agencies thereby improving the space efficiency in spatial configurations and the wayfinding system of the end-users is evidently significant in the Philippines since the country as a democratic, the government, plays a vital role in offering their services with the utmost importance in catering all the needs of the general public. On the other hand, these services are highly affected by the process on how the clients fulfill their transactions in the agencies which are currently distant or faraway from the other agencies making the clients strive more extraneous efforts in completing their undertakings thus delaying the time as well as the process consumed to finish their businesses. The study used the concept of one-stop-shop with the use of the centralization theory, as the government functions as the center of all the process extended to the other agencies in distributing the workforce for more effective service that showcases all the client?s desideratum in one place transacting concurrently, and also the other advances of the technologies which is the e-government system that succors especially during pandemic times where the risks of viral infections exists.The study aims to determine the user?s satisfaction and perception to enhance the wayfinding system of the clients in complex environments through the environmental cues, imagaeability, and legibility. The results of the study from the analysis of the data was used as the basis to formulate the architectural guidelines for the proposed government center or complex in Panabo City.
Thesis (BS Architecture)--University of the Philippines Mindanao, 2023